0430 Stress-related Sleep Reactivity Predicts Peri-partum Insomnia, Psychopathology And Suicidality. (27th April 2018) - Palagini, L; Moretto, U; Novi, M; Masci, I; Caruso, D; Drake, C L
Abstract: Introduction: Depression and anxiety symptoms are commonly experienced by women during the peri-partum period and may have negative consequences on mothers and newborns. Changes in sleep quality and especially insomnia are also typical throughout pregnancy and have been associated with adverse outcomes including peri-partum psychopathology. On this basis reasoning that identifying women at high risk of developing insomnia may have important clinical implications on maternal-fetal outcomes, we aimed to study stress-related sleep reactivity, as a risk factor to developing insomnia, and its association with peri-partum psychopathology in pregnant women. Methods: Sixty-two pregnant women (mean age 33.6 ± 3 years, 20.6 ± 0.6 weeks of pregnancy) were evaluated during their routine visit at the Gynecological Unit of the University of Pisa, Italy, using the Insomnia Severity Index (ISI) for insomnia symptoms, the Ford Insomnia Response to Stress Test for sleep-reactivity (FIRST), Edinburgh Postnatal Depression Scale (EPDS) for peri-partum depressive symptoms, Zung Self Rating Anxiety Scale (SAS) for anxiety symptoms.Item number 10 of the EPDS was used to evaluate sucidality. T test was used to calculate differences in means between women with high (FIRST score ≥ 16) vs low stress-related sleep reactivity. Unilinear/multiple and logist regressions have been performed to study correlations between variables. Results: Pregnant women with greater stress related sleep reactivity (n 29, mean age of 34.2 ± 2 years, FIRST score: 21.4 ± 2 vs 12.2 ± 4 p=0.02) presented higher scores in the EPDS (8.3 ± 5 vs 6.2 ± 4 p=0.04) in the EPDS item 10 (0.2 ± 0.8 vs 0.0, p<0.0001) and in the ISI (6.3 ± 3 vs 3.1 ± 2, p=0.02). Greater FIRST scores correlated with greater SAS (coeff: 0.30, p=0.02), ISI (coeff: 0.33, p<0.0001), EPDS (coeff: 0.22, p=0.02) scores and with greater suicidality (coeff: 0.2, p=0.03). Conclusion: Pregnant women with greater stress related sleep reactivity may suffer from greater psychopathology such as insomnia, anxiety, depressive symptoms and suicidality. It should be of importance to evaluate stress-related sleep reactivity during pregnancy to prevent and treat insomnia, psychopathology and their negative consequences on maternal-fetal outcomes. Support (If Any): no support.